Karakteristik Limbah Penebangan Kayu di Hutan Rakyat Bone Pute, Luwu Timur - Andi vika Faradiba (Jurnal Hutan dan Masyarakat, 2021)
Community forests are one of the alternative wood producers that play an important role in satisfy the requirement of industrial raw materials. Logging activities that are usually carried out in community forests can lead to the potential for waste to be generated. This study aims to identify the logging process carried out in community forests and the characteristics of the waste generated from the logging process. This research was conducted in the Community Forest of Bune Pute Village, Burau District, Luwu Timur Regency by collecting data on sample plots made by purposive sampling on a logging plot measuring 100 x 100 m. The data obtained were then analyzed using qualitative descriptive analysis. The results showed that the felling process was carried out by loggers who used chainsaws to make the fall and return notches. However, it is not always done by loggers in community forests. This is because the diameter of the stems that are cut are usually not too large. Furthermore, in the process of determining the direction of the tree's fall, the loggers consider several factors including the inclination of the canopy, the direction of the wind, and the slope of the tree trunk. The characteristics of the resulting cutting waste are stump, scion waste, and branch-free stem waste Keywords: Community Forest, Logging, Waste